APUNTES SOBRE IDENTIDAD, SOBERANÍA Y LENGUA EN LA COSMOGONÍA PERONISTA - Sagnella, Angela (Cultura Latinoamericana, 2021)
This article aims to offer an exploration into Peronism within a historical political framework in order to analyse and deepen the relationship between the construction of national sovereignty and the so-called “cuestión de la lengua”. In turn, diachronically, two main lines of thought will be highlighted: an initial one, characterised essentially by the “discurso hispanista” and another —developed around 1952— in which an Argentine linguistic autonomy is claimed, detached from the Spanish heritage and more inclined, instead, towards a Latin American political-cultural unity. Within this analysis, apart from the indoctrination found in the normative provisions of Peronism and the modelling of consciences through the educational system, this paper aims to return to the “cuestión de la lengua” in order to situate the dichotomous peculiarity of this political movement, and the importance of the policies used to construct the cultural framework and the socio-political meanings.